Air Heat Pump in Wind Power - L. I. Gretchikhin; A. I. Hutkouski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
An experimental facility has been developed and manufactured to study the disruptive flow in an air heat pump. The propeller of the heat pump does not produce pulling or pushing forces. The external air flow is created by a high speed propeller perpendicular to the plane of rotation of the heat pump propeller and acts as a ventilator. Herewith, a disruptive flow in the back side of the heat pump propeller is being created and conditions for converting the thermal component of the ventilator air flow into electrical energy by an electric power generator are realized. An aerodynamic model of the flow around the propeller blades of the heat pump in mutually perpendicular airflow has been developed. Experimental studies of the operating propeller as a heat pump, taking into account the friction during rotation of the rotor in the stator of the electric generator, were carried out. In order for the air heat pump to perceive the impacting air flow from the ventilator, it must rotate with minimal power. As a result, for two standard twin-bladed propellers mounted on a 100 W engine under the wind generated by the ventilator which speed is 2.17 m/s the conversion factor was 5.04. As the speed of air flow from the ventilator increased, the  conversion  coefficient  decreased  sharply.  When  placing  the  two  specified  propellers  on a 300 W motor, the minimum pre-rotation power was 5.7 W. In this case, when an air flow speed is of 1.08 m/s, the conversion coefficient reached only 2.93 and also fell sharply with the increase in the air flow speed. When a three-blade propeller with blades was used on a 300 W motor, then situation has changed dramatically. When the motor with a special propeller with a power of 12.1 W was spun and the air flow was formed at a speed of 3.2 m/s, the conversion coefficient was 12.4. With the reduction in the power of the spinup down to 5.9 W and in the speed of the air flow created by the ventilator to 1.7 m/s, the conversion coefficient increased to 14.9. The theoretical calculation of heat pump conversion coefficient is confirmed by experimental data. The conditions under which this coefficient reaches its maximum value are set. Computer modeling of different designs of heat pump propeller blades was performed. It is demonstrated that an air heat pump is a complex open energy system.